TINGKAT KESEJAHTERAAN ANTARA PENDUDUK ASLI DENGAN PENDUDUK PENDATANG DI KELURAHAN VI SUKU KECAMATAN LUBUK SIKARAH KOTA SOLOK - Sinaga, Ida Royani Elisabeth (STKIP PGRI Sumbar, 2014)
This study aims to determine: 1) Know the difference natives housing with migrants in theVillage District of Lubuk Sikarah VI Parts Solok. 2) Know the difference between theincome level of the natives with migrants in the Village District of Lubuk Sikarah VI PartsSolok. 3) Know the difference between the educational level of the natives with migrants inthe Village District of Lubuk Sikarah VI Parts Solok. 4) Know the difference between thelevel of health of the natives with migrants in Sub VI Parts Solok District of Lubuk Sikarah.This type of research is Descriptive Comparative Research. The population of this research isall the settlers and the indigenous people residing in the Village District of Lubuk Sikarah VIParts Solok. The sampling technique of this research is purposive sampling means samplesrondom selected based on certain considerations are 174 people. This type of data is theprimary data (ie, questionnaire) and secondary data. The results of this study indicate that: 1)There are differences in housing conditions between local people and migrants in the VillageDistrict of Lubuk Sikarah VI Parts Solok, 2) There are differences in education betweennatives with migrants in Sub VI Parts Solok District of Lubuk Sikarah,, 3) There aredifferences in income between natives with migrants in Sub VI Parts Solok District of LubukSikarah,. 4) There are differences between the health of indigenous people by the settlers inthe Village District of Lubuk Sikarah VI Parts Solok.